2011
DOI: 10.1264/jsme2.me10213
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mesorhizobium loti Genes Relevant to Symbiosis by Using Signature-Tagged Mutants

Abstract: Signature-tagged mutagenesis was applied to Mesorhizobium loti, a nitrogen-fixing root-nodule symbiont of the leguminous plant Lotus japonicus. We arranged 1,887 non-redundant mutant strains of M. loti into 75 sets, each consisting of 24 to 26 strains with a different tag in each strain. These sets were each inoculated en masse onto L. japonicus plants. Comparative analysis of total DNA extracted from inoculants and resulting nodules based on quantitative PCR led to the selection of 69 strains as being reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A large-scale transposon mutagenesis study of strain ORS278 identified 29 ndv genes that, when mutated, resulted in severely impaired nodule development by ORS278 (7,9). Unexpectedly, the BiBlast comparison revealed that most of the ndv genes (27 of the 29 genes in ORS278), including purine biosynthesis genes (34), are conserved in the S58 genome (see Table S3 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…A large-scale transposon mutagenesis study of strain ORS278 identified 29 ndv genes that, when mutated, resulted in severely impaired nodule development by ORS278 (7,9). Unexpectedly, the BiBlast comparison revealed that most of the ndv genes (27 of the 29 genes in ORS278), including purine biosynthesis genes (34), are conserved in the S58 genome (see Table S3 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…In further work, this library was used to show that ϳ2% of S. meliloti genes contribute to rhizosphere colonization ). Screening of a Mesorhizobium loti STM library on host plants identified 13 Nod − or Fix − mutants as well as 33 mutants impaired in symbiotic competitiveness (Borjigin et al 2011). Recently, a Sinorhizobium fredii STM library consisting of 25 500 mutants was reported, and an initial screen of 10% of these mutants identified four mutants impaired in symbiosis ).…”
Section: Description Referencementioning
confidence: 99%